TINDAK TUTUR EKSPRESIF MENGKRITIK DAN MEMUJI DALAM NOVEL PADANG BULAN DAN CINTA DI DALAM GELAS KARYA ANDREA HIRATA - Misra Nofrita (STKIP ROKANIA, 2016)
The novel is a literary work that is not only textual could be assessed in terms of the intrinsic structural approach, but it can also be assessed in terms oflinguistic linguistiknya. Kajian in which there are studies that examine pragmatic language activities in the world nyata.Dalam this case, researchers examineddata pragmatics textual contained in Padang Bulan novel and Love in In Glass. This study aims to (1) describe the type of speech acts expressive, (2)describes the strategy tells used in speech acts expressive. (3) describe the context of a situation which affects the use of strategies recalled in the speech actsexpressive. The research is a qualitative study using descriptive methods.